Climate-Fungal Pathogen Modeling Predicts Loss of Up to One-Third of Tea Growing Areas - Tibpromma, Saowaluck; Dong, Yang; Ranjitkar, Sailesh; Schaefer, Douglas A.; Karunarathna, Samantha C.; Hyde, Kevin D.; Jayawardena, Ruvishika S.; Manawasinghe, Ishara S.; Bebber, Daniel P.; Promputtha, Itthayakorn; Xu, Jianchu; Mortimer, Peter E.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Climate change will affect numerous crops in the future, however, perennial crops, such as tea, are particularly vulnerable. Climate change will also strongly influence fungal pathogens. Here, we predict how future climatic conditions will impact tea and its associated pathogens. We collected data on the three most important fungal pathogens of tea (Colletotrichum acutatum, Co. camelliae and Exobasidium vexans), and then modeled distributions of tea and these fungal pathogens using current and projected climates. Models show that baseline tea-growing areas will become unsuitable for Camellia sinensis var. sinensis (15 to 32% loss) and C. sinensis var. assamica (32 to 34% loss) by 2050. However, new areas will become suitable for tea cultivation, though existing and potentially new fungal pathogens will also present challenges in these areas. Protecting global tea cultivation requires innovative approaches that consider fungal genomics as part and parcel of plant pathology.